Why are lead-poisoned waterfowl rarely seen?: the disappearance of waterfowl carcasses in the Camargue, France - Pain, Deborah J (Wildfowl, 1991)
This study investigates the longevity of waterfowl carcasses in a typical wetland habitat in the Camargue, France. With a high carcass density (50 birds in 7.8 ha) scavenging rates were very rapid. Carcasses in exposed positions on land persisted for on average 1.5 days, those concealed by vegetation for 3.3 days and those exposed on water for 7.6 days. These differences are probably related to the identity and abundance of predators and scavengers and their foraging routes. The results indicate that high lead poisoning waterfowl mortality may occur unnoticed by hunters and game managers in the Camargue and other similar wetlands, mainly due to elevated rates of carcass removal by scavengers and predators.